CRISIS IN NAMUN VILLAGE: UNRAVELING PT PERTAMINA EP TANJUNG'S LEGAL OBLIGATIONS AMID CRUDE OIL PIPELINE LEAKAGE - Ahmad Iqbal Ubaidillah; Berliana Putri Nurhari; Salvia Zahra Shavalysta; Sekar Tiara Citra Maharany; Tiara Putri Fitriana (Problematika Hukum, 2024)
Amidst the serene landscapes of Namun Village in Tabalong District, a rupture in an oil pipeline has disrupted the tranquility, prompting a closer examination of the environmental ramifications and legal accountabilities of PT Pertamina EP Tanjung within Indonesia's regulatory landscape. Through qualitative normative analysis utilizing secondary data, this study delves into the aftermath of the spillage, revealing its profound impact on the local ecosystem and community. It becomes evident that PT Pertamina EP Tanjung bears a significant responsibility in averting future incidents and ensuring adherence to environmental laws. Hence, a nuanced understanding of the legal framework emerges as pivotal in enhancing environmental stewardship, fostering corporate responsibility, and advancing sustainable practices in Indonesia's extractive industries.Keywords: Cipta Kerja, Environtmental, Oil Leakage, Pertamina